Analysis of the Contribution of Micro and Small Scale Industries to Poverty Reduction in Indonesia During the 2020-2023 Period - Aqila Raeshad; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Poverty is a national challenge faced by almost every country in the world, and its resolution requires various strategic efforts from different parties. This study aims to analyze the role of the MSME sector in reducing poverty levels in Indonesia using a quantitative approach. The research utilizes panel data from 34 provinces in Indonesia for the years 2020-2023, employing the two-stage least squares (2SLS) method. The study finds that several factors influence the income of micro and small-scale industries, such as the number of industries, the percentage of paid labor, and the percentage of industries using digital technology, all of which have a positive and significant correlation. Meanwhile, the percentage of industries innovating in technology and production processes has a positive but insignificant effect on the income of micro and small-scale industries. Additionally, the correlation between micro and small-scale industry income and the percentage of the poor population shows a negative and insignificant effect.